Performance enhancement and life cycle analysis of a novel solar HVAC system using underground water and energy recovery technique. (1st December 2022) - Rahman, S.M.A.; Issa, Salah; El Haj Assad, Mamdouh; Khaleduzzaman Shah, Sheikh; Abdelkareem, Mohammad Ali; Enamul Hoque, Md.; Olabi, A.G.
Highlights: A novel solar-assisted HVAC in UAE was studied. Energy recovery and passive techniques were investigated. 31.5% space-cooling load was reduced by passive methods. A good agreement was obtained between the analytical model and the experimental results. A maximum COP of 5 was achieved compared to 3.82 in conventional system. Abstract: This study focuses on the performance analysis of a novel solar-assisted heating, ventilation, and air conditioning (HVAC) system, using R407c as a refrigerant under United Arab Emirates (UAE) climate conditions. The energy recovery techniques and explicit passive techniques were investigated for the reduction of energy consumption and overall cost by using underground water. It was found that the space-cooling load was reduced by 38.4 % with the help of distinct passive methods. The underground average water temperature is stable at 28 °C in the UAE throughout the year and thus, was used to decrease the cooling consumption. A reduction in cooling consumption and of compressor capacity of about 13 % and 10 %, respectively was achieved using these approaches. Good agreement was obtained between the analytical model and the experimental results. A comparison was also carried out between the proposed new system and the conventional system. Results indicated that the maximum COP of 5 was achieved with the proposed system, while COP in conventional system obtained 3.82. Furthermore, Eco Audit CES Edu pack software was used to analyses life cycle assessment to determine the new design's variability. Overall, the proposed new system appears to be environmentally friendly and economically viable.